Evaluation of Yield and Growth Indices of Canola (Brassica napus L.) Cultivars in Different Nitrogen Fertililization Levels - Zadeh, Mir Naser Seiedi, Raouf Seyed Sharifi, Mohammad Zaefi (Journal of Phytology, 2009)
In order to evaluation of effects of different nitrogen fertilization levels on yield and growth indices of canola (Brassica napus L.) cultivars, an split plot experiment based on randomized complete block design was conducted in Research Farm Islamic Azad University, Ardabil branch in 2007. Factors were: nitrogen fertilizer at four levels (0 as control, 50, 100 and 150 kg N/ha) in the main plots and canola cultivars at three levels (Clover, Opera and Okape) in the sub plots. The results showed that various levels of nitrogen fertilizer affected yield and growth indices of Brassica napus. Means comparisons in compound of treatment cultivar x levels of nitrogen showed that maximum grain yield was obtained by the plots which was applied 150 kg nitrogen/ha with opera cultivar. Investigation of variances trend of total dry matter indicated that in all of treatment compounds, it increased slowly until 215 days after sowing with increasing of nitrogen fertilizer and then increased rapidly till 299 days after sowing. From 299 days after sowing till harvest time, it decreased due to increasing aging of leaves and decreasing of leaf area index. Increase in N levels also significantly increased the crop growth rate and the maximum of it was observed by the plots that received 150 kg N/ha with opera cultivar. In addition, in all of treatment compounds, CGR increased slowly until 243 days after sowing and then decreased slowly till 257 days after sowing. From 257 days after sowing till harvest time, it decreased due to increasing aging of leaves and decreasing of leaf area index. Thus, it can be suggested that in order to increasing of grain yield, total dry matter crop growth rate and the other of physiological indices should be applied opera cultivar with 150 kg N ha-1 in conditions of Ardabil Plain.